Point prevalence survey is useful for introducing effective surveillance of healthcare-associated infections - Marjaana Pitkäpaasi; Jaana-Marija Lehtinen; Mari Kanerva (Elsevier, 2021)
Summary: Background: In Finland, the surveillance of healthcare-associated infections (HAI) became obligatory by the renewed Communicable Diseases Act on the 1st March 2017. Aim: To introduce HAI surveillance protocol (HALT-2 by ECDC) in primary care hospitals in the largest hospital district in Finland, and to measure the burden of HAIs and antimicrobial use patterns for improvement. Methods: Two identical point prevalence surveys (PPS) were organized in autumn 2015 and in spring 2017. The infection control persons (ICP) in the hospitals were inducted to the HAI definitions and the study protocol to collect the data with questionnaires on the study days. The data were checked and analyzed by the areal infection control unit. The hospitals were provided feedback of the results and HAI prevention methods. Findings: In 2015, 2218 patients from 22 hospitals and in 2017, 2343 patients from 25 hospitals were studied. The prevalence of HAI was 11% in both surveys (ranges per hospital 4-24% and 4-31%, respectively). Of all HAIs, 37% originated from referring hospitals. Respiratory tract, urinary tract and skin were the most frequent sites of infection. One fourth of all patients received at least one systemic antimicrobial. The process showed that recognition of HAIs may be difficult for non-experienced ICPs. Conclusions: The HALT-2 protocol proved useful in introducing HAI surveillance and prevention in primary care hospitals with active patient transfer from other hospitals and relatively high prevalence of HAI and antimicrobial use. For annually repeated surveys, slightly shorter electronic questionnaires are essential.